Revendo histórias, construindo o presente e plantando o futuro: proposta de trabalho com famílias adolescentes em situação de vulnerabilidade em Belém-PA - Bastos, Bruna Francinetti Menezes Castro (2016)
Based on systemic theory and considering that Cerveny (1997) conceives the adolescent stage of the vital cycle of the family as the period in which the whole family act as a teen, this study aims, through qualitative research, understand how it develops this process in vulnerable households attended by Social assistance Reference Centers (CRAS) of Aurá and Guama in Belem – PA; we also present a proposal for intervention for families with such features. The studied population was composed of 33 participants from 10 families, and 6 from CRAS Aurá and 4 from CRAS Guama. Data collection consisted of 20 meetings, 10 in each center. We use the following instruments: one form with 71 questions concerning the structure and dynamics of the adolescent´s family; an Interview semi-structured with 9 questions; and 9 workshops with multi-family groups. The results revealed that, in the adolescent phase of the family vital cycle, it is necessary to create new rules as a way of adapting each member to perform his duties in the family because the family roles are well definied. The father provides the household. The mother is responsible for taking care of home and children, even when also has a job. Adolescents must obey the rules, collaborate in domestic activities, studying and caring for parents and grandparents when these become ill. Grandmothers living with their teenage grandchildren build personal relationships and care for the teens. The intervention proposal considered not only the recommendations of the Unified Social Assistance System (SUAS) to work with families in vulnerable situations, but also the intergenerationality, the different family structures, the local culture, the knowledge of the family and the demands by them. We seek to emphasize the potential of the surveyed families and to build strategies of dealing with adverse situations anda encouraging the active participation of its members. For the participants, the intervention allowed them to realize they are not a single case; besides, it extended the support network, encouraged them to learn as they shared their stories and strengthened their family bonds. Adolescents identified with the presented issues, said the intervention favored relationship and family communication, and the recognition of its inter-generational inheritance. Adults felt supported and highligted the importance of having access to information to facilitate the performance of their roles in the family and community. As for their life project, the families surveyed had difficulty in planning it, especially adults. Based on this experience, it was observed that the vulnerability also affects the professionals who work with these families. The strengthening of public policies that take care of professionals working with families in vulnerable situations is required. We hope that the knowledge produced in this study encourage the practice to consider the context and the diversity of the Brazilian family in contemporary society